(untitled) - Williams, Richard H. (Pacific Grove, CA, 2003)
This book focuses on teaching probabilistic and statistical methods to upper-division electrical and computer engineering (EECE) students. The first part of the book, Chapters 1-3, contains fundamental probability material. The second part, Chapters 4-7, presents applications and extensions based upon the first three chapters. The four application chapters may be studied in any order, as they do not depend on each other in any essential way
Keywords: Engineering,Probabilities,Xác suất,Kỹ thuật; Statistical methods,phương pháp thống kê